1986
DOI: 10.1172/jci112378
|View full text |Cite
|
Sign up to set email alerts
|

Activation during ventricular defibrillation in open-chest dogs. Evidence of complete cessation and regeneration of ventricular fibrillation after unsuccessful shocks.

Abstract: To test the hypothesis that a defibrillation shock is unsuccessful because it fails to annihilate activation fronts within a critical mass of myocardium, we recorded epicardial and transmural activation in 11 open-chest dogs during electrically induced ventricular fibrillation (VF). Shocks of 1-30 J were delivered through defibrillation electrodes on the left ventricular apex and right atrium. Simultaneous recordings were made from septal, intramural, and epicardial electrodes in various combinations. Immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
1
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(111 citation statements)
references
References 37 publications
8
99
1
3
Order By: Relevance
“…Of the 24 successful shocks, 22 were Type B successes, which are defined as successful defibrillation shocks with the earliest first post-shock activation recorded in the working myocardium within 130 ms of the defibrillation shock. 15 Type A successes, which are defined as successful defibrillation shocks after which this interval is >130 ms, occurred twice and had an average earliest recorded post-shock activation time of 245 ms. The first five post-shock activation cycles in these two episodes were all sinus beats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 24 successful shocks, 22 were Type B successes, which are defined as successful defibrillation shocks with the earliest first post-shock activation recorded in the working myocardium within 130 ms of the defibrillation shock. 15 Type A successes, which are defined as successful defibrillation shocks after which this interval is >130 ms, occurred twice and had an average earliest recorded post-shock activation time of 245 ms. The first five post-shock activation cycles in these two episodes were all sinus beats.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15] Previous defibrillation studies have demonstrated that in pigs first postshock activation tends to arise closer to the epicardium than the endocardium.11 , 16 In pigs, Purkinje fibers traverse the ventricular wall and extend nearly to the epicardial surface. [17][18][19] Thus, the subepicardial location of the first recorded post-shock electrical activation in pigs raises the possibility that the earliest post-shock activation arises in the specialized conduction system.…”
Section: Introductionmentioning
confidence: 99%
“…These results may also explain phenomenon of the "iso-electric window", which was observed after failed defibrillation shocks. (35) …”
Section: Discussionmentioning
confidence: 99%
“…Monophasic shocks may be strong enough to terminate the wavefronts of VF, but fail to defibrillate because the shocks create virtual electrodes, which generate new wavefronts that reinitiate VF (60,61). Figure 11 shows the development of a virtual cathode and anode on the anterior epicardium of an optically mapped rabbit heart (62).…”
Section: Global Mechanisms Of Defibrillationmentioning
confidence: 99%